Real Estate Volatility and Economic Stability: An East Asian Perspective - Man Cho; Kyung-Hwan Kim; Bertrand Renaud (Korea Development Institute (KDI), 2012)
East Asia, which houses 22% of the total world population, has been experiencing an explosive and sustained output growth in the post World War II era. Besides the rapid economic growth, the region is also characterized by a high population density, with a density of 350 persons per square mile, about three times higher than the world average. In the process of the growth, and the industrialization and urbanization that came with it, the primate cities and other major urban areas in the region often faced with chronic shortage of land and real estate space, causing a rampant appreciation of property value. That, in turn, contributed to a rise of speculative demand for housing and unaffordable shelter for low and moderate income households. In the supply side, various natural as well as man-made constraints made the supply response inelastic and exacerbated the price volatility and housing affordability. Furthermore, thanks to the liberalization of financial markets, the residential mortgage lending sector has been rapidly evolving, which raised the affordability of home purchase for low-income and less-creditworthy borrowers on the one hand but also made it more likely to have an inter-sectoral contagion between housing and macro-economy in those countries, both in upturns and in downturns. This study aims to offer comparative analyses on real estate sectors of six East Asian (EA) countries – China, Hong Kong, Japan, Korea, Singapore and Taiwan – by: (1) documenting episodes of housing price boom-bust as identified in the literature; (2) performing data analyses, both exploratory and explanatory, on determinants of housing price dynamics in the study area; and, (3) investigating institutional factors of relevancy observed from those countries. In so doing, we put an extra effort to cover both market fundamentals and key institutional aspects of real estate system by focusing on land and housing supply, mortgage lending, and real estate taxation.
Keywords: 330